Benefits and costs of debt: The dose makes the poison - M. Ayhan Kose; Franziska Ohnsorge; Naotaka Sugawara (Koç University-TÜSIAD Economic Research Forum (ERF), 2020)
Government debt has risen substantially in emerging market and developing economies (EMDEs) since the global financial crisis. The current environment of low global interest rates and weak growth may appear to mitigate concerns about elevated debt levels. Considering currently subdued investment, additional government borrowing might also appear to be an attractive option for financing growth-enhancing initiatives such as investment in human and physical capital. However, history suggests caution. Despite low interest rates, debt was on a rising trajectory in half of EMDEs in 2018. In addition, the cost of rolling over debt can increase sharply during periods of financial stress and result in financial crises; elevated debt levels can limit the ability of governments to provide fiscal stimulus during downturns; and high debt can weigh on investment and long-term growth. Hence, EMDEs need to strike a careful balance between taking advantage of low interest rates and avoiding the potentially adverse consequences of excessive debt accumulation.
Keywords: E62; H62; H63; 330; Debt sustainability; fiscal balance; government debt; optimal debt level; private debt